2022
DOI: 10.3389/fpls.2021.802802
|View full text |Cite
|
Sign up to set email alerts
|

S1-bZIP Transcription Factors Play Important Roles in the Regulation of Fruit Quality and Stress Response

Abstract: Sugar metabolism not only determines fruit sweetness and quality but also acts as signaling molecules to substantially connect with other primary metabolic processes and, therefore, modulates plant growth and development, fruit ripening, and stress response. The basic region/leucine zipper motif (bZIP) transcription factor family is ubiquitous in eukaryotes and plays a diverse array of biological functions in plants. Among the bZIP family members, the smallest bZIP subgroup, S1-bZIP, is a unique one, due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 131 publications
0
11
0
Order By: Relevance
“…Of these, it was worth noting that the TFs predicted in FaERF118 promoters such as TCP15 were annotated to act as a repressor of anthocyanin accumulation [19] and GLK1 was annotated to be the activator of chlorophyll biosynthesis [20]. ABI4 predicted in FaERF316 promoter was a critical downstream component of ABA signaling in plant [21,22], while bZIP53 could affect plant sugar accumulation [23,24]. Note: the TFs in the bracket were the best hit in Arabidopsis.…”
Section: Regulatory Mechanism Analysis In the Promoter Regions Of Fae...mentioning
confidence: 99%
“…Of these, it was worth noting that the TFs predicted in FaERF118 promoters such as TCP15 were annotated to act as a repressor of anthocyanin accumulation [19] and GLK1 was annotated to be the activator of chlorophyll biosynthesis [20]. ABI4 predicted in FaERF316 promoter was a critical downstream component of ABA signaling in plant [21,22], while bZIP53 could affect plant sugar accumulation [23,24]. Note: the TFs in the bracket were the best hit in Arabidopsis.…”
Section: Regulatory Mechanism Analysis In the Promoter Regions Of Fae...mentioning
confidence: 99%
“…bZIP transcription factor regulates their target genes on their promoters and thereby direct adjusts plant developmental and abiotic stresses, such as drought, salinity, and cold. S1-bZIP is a unique one, which conserved upstream open reading frames mediate Sucrose-Induced Repression of Translation(SIRT), maintain sucrose homeostasis and withstand abiotic stresses in plants [ 22 ]. LcMYB2 promoted seed germination and root growth under drought and ABA treatments.…”
Section: Resultsmentioning
confidence: 99%
“…The two enzymes pyrroline-5-carboxylate synthetase (P5CS; EC not assigned) and pyrroline-5-carboxylate reductase (P5CR; EC 1.5.1.2) are involved in proline biosynthesis catalyzing glutamate to proline [ 29 , 31 ]. In Arabidopsis , S 1 -bZIPs, including bZIP2, bZIP11, bZIP44, and bZIP53, function as transcriptional activators of ProDH genes [ 33 ], and the formation of the C/S 1 bZIP network is required for controlling ProDH expression [ 11 ]. Here we showed that N .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, improving heat tolerance is of profound importance to the production yields of crops and will greatly secure food security [ 41 ]. Plant S 1 -bZIPs play a key role in plant innate immunity and the response to unfavorable environmental conditions [ 11 ]. In our previous study, BrbZIP-S was induced under abiotic stress conditions [ 13 ], indicating the possible involvement of BrbZIP-S in the stress response.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation